2014
DOI: 10.1159/000375258
|View full text |Cite
|
Sign up to set email alerts
|

Is the BFM Regimen Feasible for the Treatment of Adult Acute Lymphoblastic Leukemia? A Retrospective Analysis of the Outcomes of BFM and Hyper-CVAD Chemotherapy in Two Centers

Abstract: Multiple induction regimens have been developed for adult patients with acute lymphoblastic leukemia (ALL). However, there have been no prospective randomized trials that directly compare these regimens. In this study, we wanted to evaluate the outcome of 50 adult ALL patients treated with BFM (i.e. Berlin-Frankfurt-Munster, n = 20) and hyper-CVAD (n = 30) protocols between March 2006 and October 2012. The median age was 25 years in the BFM group and 30.5 years in the hyper-CVAD group with a male/female ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
(22 reference statements)
6
24
0
Order By: Relevance
“…This study had limitations as a result of its retrospective nature, small numbers, and a selection bias for different treatment regimens. 17 However, similar to the report by Buyukasik et al, 9 Alacacioglu et al 14 also reported a superior 5-year OS rate using a Berlin-Frankfurt-Münster regimen (n = 20) compared with the more intensive HCVAD regimen (n = 30; 59% v 34%, respectively). A common theme in these reports was the significant challenge in intensifying the chemotherapy regimens in adult patients with ALL in a developing country.…”
Section: Introductionsupporting
confidence: 64%
“…This study had limitations as a result of its retrospective nature, small numbers, and a selection bias for different treatment regimens. 17 However, similar to the report by Buyukasik et al, 9 Alacacioglu et al 14 also reported a superior 5-year OS rate using a Berlin-Frankfurt-Münster regimen (n = 20) compared with the more intensive HCVAD regimen (n = 30; 59% v 34%, respectively). A common theme in these reports was the significant challenge in intensifying the chemotherapy regimens in adult patients with ALL in a developing country.…”
Section: Introductionsupporting
confidence: 64%
“…However, a lower 5-year OS rate was seen in patients treated on hyper-CVAD compared with CALGB-8811 (26% vs. 44%, respectively). Similarly, a recent report from Alacacioglu et al 62 found similar CR rates after induction therapy for patients treated with BFM or hyper-CVAD protocols (95% and 96%, respectively). However, patients in the BFM group showed higher 5-year survival rates compared with the hyper-CVAD group (59% vs. 34%, respectively).…”
Section: Treatment Of Aya Patients With Allsupporting
confidence: 53%
“…There was no difference between two protocols in terms of adverse effects. 12 In our present study, BFM-95 was better than Hyper-CVAD as well.…”
Section: Discussionsupporting
confidence: 61%